Network structure and mechanical properties of hydrophobic association hydrogels: Surfactant effect I. Issue 1 (25th July 2014) - Liu, Chang; Liu, Xiaoli; Yu, Jingfeng; Gao, Ge; Liu, Fengqi
ABSTRACT Three series hydrophobic association hydrogels (HA‐gels) with different concentration of sodium dodecyl sulfate (SDS) were prepared by free radical micellar copolymerization. The backbone of HA‐gels was based on the copolymer of acrylamide and a little octylphenol polyoxyethylene ether acrylate with 10 ethoxyl units (OP10∼AC). Their mechanical properties were determined by tension tests. It was found that the properties of all three series HA‐gels presented a very similar variation tendency with increasing R, the molar ratio of SDS to OP10∼AC. In the medium region of R (around 1.23), higher effective crosslinked density and proper match between shorter and longer chains were achieved, so that the HA‐gels exhibited better mechanical strengths. In lower R region, it is prone to form the unstable aggregation of OP10∼AC with little SDS, while in higher R region some of co‐micelles could not act as crosslinkers. Both would reduce the effective crosslinked density and the mechanical strength of HA‐gel. In the condition of fixed R, the change of OP10∼AC content would remodel the topological structure of network. The HA‐gels with better properties could be obtained as the OP10∼AC content was varied from 1 to 2% at the proper R. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41222.